The influence of parenting style and family meals on body esteem among Costa Rican adolescents - Rafael Monge-Rojas; Vanessa Smith-Castro; Rulamán Vargas-Quesada (International Journal of Adolescence and Youth)
The psychological wellbeing of adolescents is significantly influenced by their body esteem, which is shaped by various factors. This study aims to examine how parenting styles impact adolescent body esteem, considering the potential mediating effect of family meals. Initially, a complex model was tested but found to be an inadequate fit (χ2) = 299.18, df = 12, p < 0.001, CFI = 0.74, TLI = 0.30, GFI = 0.99, RMSEA = 0.21). Subsequently, a data-driven reduced model was analysed, showing excellent fit (χ2 = 21, df = 3, p < 0.001, CFI = 0.98, TLI = 0.92, GFI = 1.00, RMSEA = 0.10). This model revealed that authoritative parenting fosters a positive family meal atmosphere, thus enhancing adolescent body esteem. However, adolescent participation in family meals was low. Public health stakeholders must devise strategies aimed at promoting the active engagement of both parents and adolescents in family meals.